Oxidative stabilization of corn oil with spinach extract (Bangladesh Journal of Scientific and Industrial Research, 2019)
The present study was aimed to analyze the antioxidant activity of spinach (Spinacia oleracea) extract in oxidative stabilization of refined, bleached and de-odorized (RBD) corn oil (CO). Corn oil was supplemented with three different concentrations 600, 1200 and 1800 ppm of methanolic spinach extract and then stored at 25oC and 60oC. Different oxidation measuring parameters such as peroxide value (PV), free fatty acid (FFA) value, iodine value (IV), conjugated dienes (CD), conjugated trienes (CT) and para-anisidine value (PAV) were examined. The potency of spinach extract as natural antioxidant was found to be as effective as the synthetic antioxidants BHA and BHT used as standards and highest stabilization was observed in the order CO-1800>CO-1200>CO-BHT> CO-BHA>CO-600>CO-control. The results showed a significant effect of spinach extract in enhancing the oxidative stability of corn oil.Bangladesh J. Sci. Ind. Res.54(4), 375-382, 2019